PENGARUH IKLAN TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN - Ardian Maxelian; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2017)
Republika Newspaper is one national newspaper widely circulated in several area in Indonesia one of them is DKI Jakarta Province. The rapid development Republika Newspaper it turns out there are problems in sales fluctuant past several years. The purpose of doing research is to know the influence of advetising on customer satisfaction through purchase decision on Republika Newspaper. The sample in this study amounted to 100 respondents using purposive sampling method. Analysis of the data in this study using a test validity, reliability, linear regression analysis, significance test and determination with SPSS 23. The influence of mediation evidenced by Sobel method and path analysis. The result of this study indicate that (a) advertising significantly influence to purchase satisfaction of 0,648. (b)Advertising significantly influence to customer satisfaction of 0,376. (c) Purchase decision significantly influence to customer satisfaction of 0,391. (d) And the calculation result of path analysis, advertising significantly infuence to customer satisfaction through purchase decision of 0,376296. The suggestions for improving advertising quality to improve purchase decision and maintain customer satisfacion.